213 Use of A novel peptide ligand targeting multiple immune checkpoints: a novel approach to immunotherapy against central nervous system tumors. (10th December 2020) - Moertel, Christopher; Xiong, Zhengming; Olin, Michael
Abstract : Background: Cancer immunotherapy has revolutionized clinical management of malignancies by generating long-term, durable control of tumors, rendering more manageable diseases that previously had dismal prognoses. Unfortunately, these therapies often enhance autoimmunity, causing serious immune-related adverse events. In addition, little efficacy is noted in CNS tumors. Our research is focused on the CD200 immune checkpoint, which modulates the immune system through the inhibitory receptor (CD200R1) and activation receptors (CD200AR). We have demonstrated that targeting the CD200AR with a peptide ligand (CD200AR-L) activates the immune system, rendering it impervious to the inhibitory effects of CD200. In a clinical trial studying canine spontaneous high-grade glioma, CD200AR-L administered with tumor autologous tumor lysate resulted in a 20% two-year progression-free survival. No adverse effects were observed. We suggest this result is due to the ability of the CD200AR-L to modulate multiple immune checkpoints. During the characterization of the CD200AR-L, we discovered that signaling molecules are shared by CD200 and PD-1/PD-L1, suggesting these important immune checkpoints are interconnected. Methods: CD200R1KO macrophages were used to determine the connection between the CD200 and PD-1 checkpoints. Next, we analyzed signaling molecules activated in CD11b cells pulsed with PD-L1 ± CD200AR-L, followed up with in vitro and in vivo effects of CD200AR-L on the expression of PD-1/PD-L1 and CTLA-4. Finally, we analyzed the ability of the CD200AR-L to surmount the suppressive effects of PD-L1. Results: Our studies demonstrate that the inhibitory CD200R1 and PD-1 mediate immune checkpoint signaling activities through SHIP1 protein. Moreover, CD200AR-L overpowers the suppressive effects of CD200 and PD-L1, which are both shed by tumors, by downregulating the inhibitory CD200R1 and PD-1 on both antigen-presenting cells (APC) and T-cells (figure 1 ), In addition, CD200AR-L downregulates PD-1 on APCs and inhibits the upregulation of PD-L1 and CTLA4. Conclusions: These studies led to the discovery that this novel peptide modulates the CD200, PD-1/PD-L1 and CTLA-4 pathways, providing the basis for the translatable development of a novel CD200 peptide inhibitor for clinical use against multiple tumors, including gliomas. These studies led to the FDA approval for the first in human peptide checkpoint inhibitor to initiate a phase I single center, open-label, dose-escalation clinical trial in adult patients with recurrent glioblastoma, to be followed by a clinical trial for children with recurrent malignant brain tumors.